Primary extracutaneous mlignant melanoma: a comprehensive review with emphasis on treatment - Figl, Adina; Schadendorf, Dirk (Onkologie, 2004)
Extracutaneous malignant melanomas (EMM) require special consideration in the field of oncology due to their rareness and - depending on the localization - the frequency of late diagnosis with consecutive poor prognosis. Only 4-5% of all primary melanomas do not arise from the skin. Most frequently they originate from the mucous membranes lining the respiratory, digestive, and genitourinary tracts or in the eyes as well as in the cerebral meninges. Extracutaneous melanomas are considered to be biologically more aggressive than cutaneous melanomas. The Clark level and Breslow index used for evaluation of cutaneous melanomas are not applicable to EMM and, at present, there are no consistent, internationally accepted therapy standards for this form of the disease. For this reason, this review focuses primarily on the literature pertaining to therapeutic strategies as well as epidemiologic, biological, and diagnostic aspects of this disease.